1998
DOI: 10.1029/98gl52361
|View full text |Cite
|
Sign up to set email alerts
|

High resolution mapping of TEC perturbations with the GSI GPS Network over Japan

Abstract: Abstract. Two-dimensional total electron content (TEC)perturbations

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
314
1
1

Year Published

2001
2001
2014
2014

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 289 publications
(321 citation statements)
references
References 26 publications
5
314
1
1
Order By: Relevance
“…In converting slant TECs to vertical ones, the contribution of electrons to the slant TECs is assumed to be entirely from a virtual thin layer at an altitude of 300 km. This is the same method as that developed by Saito et al (1998). Figure 8 shows the temporal variations of TEC perturbation along the line passing through the region observed by the MU radar which is drawn in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In converting slant TECs to vertical ones, the contribution of electrons to the slant TECs is assumed to be entirely from a virtual thin layer at an altitude of 300 km. This is the same method as that developed by Saito et al (1998). Figure 8 shows the temporal variations of TEC perturbation along the line passing through the region observed by the MU radar which is drawn in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Compared with those in the E-region, such as quasi-periodic (QP) echoes associCorrespondence to: S. Saito (susaito@enri.go.jp) ated with the sporadic-E (E s ) layer , they have not been studied well. Only a few studies in Japan (Fukao et al, 1988Saito et al, 1998Saito et al, , 2002 and in Puerto Rico (Swartz et al, 2000) using radars have reported the mid-latitude F-region FAIs. This is partly because the echoes associated with the mid-latitude F-region FAIs are relatively weak and a powerful radar is required to observe them.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The field-of-view at 250km altitude was about 1.2 x 106 square kilometer for FRONT-1 and 1.7 x 106 square kilometer for FRONT-2. GEONET, a GPS receiver network operated by the Geographical Survey Institute, was used to observe the total electron content (TEC) of the ionosphere over Japan with a 30 second time resolution [Saito et al, 1998b]. In addition to these wide coverage observations, the MU radar was used to observe coherent echoes from F-region field-aligned irregularities at 46.5 MHz frequency.…”
Section: Observationsmentioning
confidence: 99%
“…Either global or regional GPS network has contribute to this research with different time and spatial resolution. (Wilson et al, 1995;Musman et al, 1997;Saito et al, 1998;Leonovich et al, 2000). Recently, following the increase of the density of the worldwide GPS network, and of the regional GPS networks like GEONET of Japan which has the average interstation distance as short as 25 kilometers (Miyazaki et al, 1997), the ionospheric irregularities have been studied with very high time resolution and spatial resolution as well as the high precision (Afraimovich et al, 2000;Ostuka et al, 2002).…”
Section: Introductionmentioning
confidence: 99%